INTERNALISASI NILAI-NILAI MODERASI BERAGAMA DI INSTAGRAM - Yusnawati Yusnawati; Ahmad Wira; Afriwardi Afriwardi (Tatar Pasundan: Jurnal Diklat Keagamaan, 2021)
The latest highlight of religious moderation is the rise of contemporary issues of religious tolerance on social media. On that basis, this study aims to study religious studies on Instagram as one of the accountable social media platforms among the younger generation. Qualitative research design is used by literature study method. Data collection includes written documentation of Instagram content, comments. Content analysis techniques are used in primary sources related to the topic. This study confirms that Instagram has a positive impact in the process of internalizing religious moderation values among the younger generation. It is demonstrated through enthusiasm and response to the content material published by various da'wah media accounts. This study recommends subsequent research to identify the effectiveness of da'wah accounts that provide education in religious moderation. Keywords: Young generation; Instagram; Religious Moderation